KONSTRUKSI SOSIAL REVOLUSI HIJAU DI ERA ORDE BARU - Wahyu Budi Nugroho (SOCA: Jurnal Sosial Ekonomi Pertanian, 2018)
This paper seeks to examine the application and implications of the GreenRevolution in the country through the perspective of social construction Mary E.Pettenger. In her analysis, the perspective of Pettenger's social construction involvesthe dimensions of power, knowledge, social norms, and discourse or discourse. InIndonesia, the Green Revolution is better known as "Panca Usaha Tani" which issensitive to the modernization or mechanization of agriculture. Through the studiesthat have been carried out, it is clear if the “Orde Baru” regime uses resources ofpower, knowledge, social norms, and discourse in an effort to promote themechanization of agriculture in the country. A series of dimensions are arranged intoa form of social construction that successfully hides various hidden interests in it,among others; national socio-political stability, the legitimacy of debts on the part ofthe parties, alignments with the West Bloc, and efforts to make Indonesia a rice barnfor developed countries.